2008
DOI: 10.1111/j.1471-4159.2008.05640.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophin receptor RPTP‐ζ/β expression is up‐regulated by l‐DOPA in striatal medium spiny neurons of parkinsonian rats

Abstract: l‐DOPA is still the drug of choice to treat Parkinson’s disease although adverse side effects appear after several years of treatment. These are thought to be the consequence of plastic re‐arrangements of the nigrostriatal connections, such as sprouting of the dopaminergic terminals or post‐synaptic changes. Pleiotrophin, a trophic factor that we have shown to be up‐regulated in the striatum of parkinsonian rats after long‐term l‐DOPA treatment may play a role in these plastic changes. To determine whether one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…18,19 However, no study has previously examined whether nigral neurons express the ALK receptor, and only the ALK receptor has been definitively linked to PTN’s trophic effects. 20 Therefore, in an effort to determine whether PTN could potentially exert protective abilities through ALK receptors on DA neurons, SNpc neurons were immunofluorescently double labeled for TH and ALK and visualized using confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 However, no study has previously examined whether nigral neurons express the ALK receptor, and only the ALK receptor has been definitively linked to PTN’s trophic effects. 20 Therefore, in an effort to determine whether PTN could potentially exert protective abilities through ALK receptors on DA neurons, SNpc neurons were immunofluorescently double labeled for TH and ALK and visualized using confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Considering our previous results showing upregulation of the PTN-RPTPζ/β pathway in L-DOPA treated rats [34] and that RPTPζ/β modulates Fyn phosphorylation in response to PTN [47], it is also tempting to speculate a role for these molecules in L-DOPA induced plasticity, probably through the modulation of Fyn activity.…”
Section: Discussionmentioning
confidence: 96%
“…Briefly, three categories of AIMs were observed Immunohistochemistry: From the totality of mice included into the analysis of AIMs, twenty per genotype were perfused transcardially with 4% paraformaldehyde 1 h after the last dose of L-DOPA (the remaining 10/genotype were prepared for WB). Brains were processed, and immunodetection performed in both striatum and substancia nigra as previously reported [33,34]. Briefly, 30 μm free-floating coronal sections were incubated with the following primary antibody: rabbit anti-tyrosine hydroxylase (Pel-Freez Biologicals USA Cat# P40101 RRID:AB_2313713; TH, 1/1000) and rabbit anti-FosB/ΔFosB (Santa Cruz Biotechnology Cat# sc-48 RRID:AB_631515; 1/10000).…”
Section: Dopaminergic Depletion With 6-hydroxydopamine (6-ohda)mentioning
confidence: 99%
“…It was found that PTN and MK regulate the reninangiotensin II pathway in vivo [40,41], which was then linked to the capacity of PTN to generate new functional vasculature in vivo [42], an event that, when occurring within the brain, may be key for PTN neuroprotective functions [43]. In addition, it was also found that PTN and MK regulate the catecholamine biosynthesis in those transcriptional studies [44,45].…”
Section: Pleiotrophin a Cytokine With Multiple Repair Functions Withmentioning
confidence: 97%
“…In an attempt to uncover the mechanisms involved in these L-DOPA effects, Ferrario and colleagues [56] performed an analysis of differential gene expression in the striatum of L-DOPA-treated rats with partial lesions of the nigrostriatal system, identifying PTN as one factor highly upregulated in this model. Importantly, the levels of RPTP / have recently been found to be increased in the dopaminergic neurons of the substantia nigra and their targets, the striatal medium spiny neurons, of L-DOPAtreated Parkinsonian rats [43] that could potentially lead to changes in the phosphoproteome in brain areas of these L-DOPA-treated Parkinsonian rats. This hypothesis may be important since L-DOPA effects on the recovery of dopaminergic nerve terminals have been paralleled with altered protein phosphorylation [57].…”
Section: Does Ptn Have a Role In Parkinson´s Disease?mentioning
confidence: 99%